Multimaterial cryogenic printing of three-dimensional soft hydrogel machines - Jinhao Li; Jie Cao; Rong Bian; Rongtai Wan; Xiangyang Zhu; Baoyang Lu; Guoying Gu (Nature Communications)
Abstract Hydrogel-based soft machines are promising in diverse applications, such as biomedical electronics and soft robotics. However, current fabrication techniques generally struggle to construct multimaterial three-dimensional hydrogel architectures for soft machines and robots, owing to the inherent hydrogel softness from the low-density polymer network nature. Herein, we present a multimaterial cryogenic printing (MCP) technique that can fabricate sophisticated soft hydrogel machines with accurate yet complex architectures and robust multimaterial interfaces. Our MCP technique harnesses a universal all-in-cryogenic solvent phase transition strategy, involving instant ink solidification followed by in-situ synchronous solvent melting and cross-linking. We, therefore, can facilely fabricate various multimaterial 3D hydrogel structures with high aspect ratio complex geometries (overhanging, thin-walled, and hollow) in high fidelity. Using this approach, we design and manufacture all-printed all-hydrogel soft machines with versatile functions, such as self-sensing biomimetic heart valves with leaflet-status perception and untethered multimode turbine robots capable of in-tube blockage removal and transportation.